Karya sastra sebagai sarana literasi politik: Novel “Bungkam Suara" karya J. S. Khairen sebagai narasi melawan propaganda terkomputasi - Awa, Charisse Renica Benedicta; Widjayanto, Febby R. (Jurnal Politik Indonesia (Indonesian Journal of Politics), 2024)
This research examines use of literary works as a means of political literacy, specifically as a response to computational propaganda as a major challenge in the politics of the 21st century. Various previous studies regarding political literacy put emphasis on formal institutional approaches through formal education in schools which have numbers of problems, such as time, limited access, and state indoctrination. This research explores how reading texts helps citizens to read social phenomenon by reviewing theories regarding political literacy and critical literacy by using interpretive content analysis method which involves author's interpretation. The analysis shows the harmony between the narrative in the novel "Bungkam Suara" with various studies on computational propaganda and "Bungkam Suara" as counter-narrative to computational propaganda by raising readers’ awareness of their relation as netizens to the computational propaganda. Therefore, literary works can serve as an alternative in political literacy by providing different perspectives and building citizens' critical thinking over politics.